Machiavellian Political Manual in Politics: A Study of Malaysian Political Realism as Reflected in Paradoks - Sohaimi Abdul Aziz (Kajian Malaysia, 2020)
Paradoks by Affifuddin Omar is a novel discussing the issue of Malay Muslim politicians who have strayed from the norms and practices of Islam in thought and deed yet are still accepted as leaders by the Malay Muslim community. Albeit a work of fiction, this novel is accurate in its portrayal of the paradox that is Malay realpolitik. Therefore, this article aims to study the political manoeuvres used by some present-day Malay political leaders in carrying out their responsibilities in an attempt to discover why such leaders still enjoy the support of the populace. A reading approach incorporating textual and political contextual analysis will be applied to analyse the novel. Through this analysis, it is found that the Malay political leaders in the novel subscribe to Machiavellian politics, which upholds that “politics have no relation to morals”. As a result, upright Malay political leaders in Paradoks such as Ariffin, who strives for justice and adheres to Islamic and moral values, seem to have no place in Malaysian politics. This situation is exacerbated when the Malay community is more concerned over sensationalised sexual issues than most alarming issues such as corruption and abuse of power. Eventually, these unworthy leaders still command the support of the people, although they are corrupted and immoral beings. As such, the novel presents an image of a Malay Muslim population that has lost its moral compass despite an outward appearance of adhering to the tenets of the religion. This is the paradox, and this is the reality presented in the novel.